Zero days [compact disc, unabridged] - Ware, Ruth (Simon & Schuster Audio, 2023)
Hired by companies to break into buildings and hack security systems, Jack and her husband, Gabe, are the best penetration specialists in the business. But after a routine assignment goes horribly wrong, Jack arrives home to find her husband dead. To add to her horror, the police are closing in on their suspect her. Suddenly on the run and quickly running out of options, Jack must decide who she can trust as she circles closer to the real killer in this unputdownable and heart-pounding mystery from an author whose "propulsive prose keeps readers on the hook and refuses to let anyone off until all has been revealed" (Shelf Awareness).